Baculovirus vector for gene delivery and vaccine development. (January 2008) - Tani, Hideki; Abe, Takayuki; Matsunaga, Tomoko M; Moriishi, Kohji; Matsuura, Yoshiharu
The baculovirus Autographa californica multiple nucleopolyhedrovirus has been widely used not only to acheive a high level of foreign gene expression in insect cells, but also for efficient gene transduction into mammalian cells. Recombinant and pseudotyped baculoviruses possessing chimeric or foreign ligands have been constructed to improve the efficiency of gene transduction and to confer specificity for gene delivery into mammalian cells, respectively. Baculoviral DNA CpG motifs induce proinflammatory cytokines through a Toll-like receptor (TLR9)/MyD88-dependent signaling pathway. Other baculovirus components produce type I interferons via a TLR-independent pathway. Baculovirus exhibits a strong adjuvant property and recombinant baculoviruses encoding microbial antigens elicit antibodies to the antigens and provide protective immunity in mice. This review deals with recent progress in the application of baculovirus vectors to gene delivery and vaccine development, and discusses the future prospects of baculovirus vectors.